The predictive ability of demographic and psychosocial risk factors, school-related characteristics, and service interventions on grade attainment among at-risk elementary school children in a truancy intervention program - Rhodes, Judith L. F. (2011)
The purpose of the current exploratory-descriptive retrospective study was to examine the demographic, school-related, and psychosocial risk factors among at-risk elementary school children (N = 12644) assessed at low and high levels of risk for continuing truancy. The sample was enrolled in 16 statewide program sites of a community-based truancy prevention program in Louisiana, which provided a letter and attendance monitoring for low-risk participants and intensive case management for high-risk participants. Intercorrelations among risk factors and referred services and on-time grade attainment were assessed for a subsample of the high-risk children (n = 6088). Binary logistic regression analyses were conducted to determine which correlates among the demographic, school-related, and psychosocial risk factors and services best predicted on-time grade level at 3 years out among a subsample of the high-risk children (n = 2864). Model fit to the data was modest. Findings showed that race and grade at program admission were significantly associated with on-time grade attainment at 3 years out. African-American participants were less likely to be on time for grade than participants not of African-American ethnicity. Participants in kindergarten were less likely to be on time than children in higher grades of elementary school. Children assessed as unmotivated by their teachers were less likely to be on time for grade at 3 years out than children who were not assessed as unmotivated. Other findings showed that participants who completed educational services were less likely to be on time for their grade than participants who did not receive educational services. Implications for social work practice, education, and research are discussed